(untitled) (Papeles, 2017)
The main purpose of this research is to determine the added value of the majors offered by the Faculty of Economical Sciences at the National University (at the Bogotá campus), taking as a main reference the component of critical reading in the Saber Pro exams developed between 2008 and 2015. Thus it is proposed a mix methodological approach (cualitative-cuantitative), using demographic, socioeconomic and institutional variables, which will allow us to reveal how meaningful is the academical contribution offered by that university to the society (in the educational field), and just like the quality of the knowledge acquired by its graduates (in terms of the component proposed).